Maintenance rituximab or observation after frontline treatment with bendamustine‐rituximab for follicular lymphoma. (21st December 2018) - Hill, Brian T.; Nastoupil, Loretta; Winter, Allison M.; Becnel, Melody R.; Cerhan, James R.; Habermann, Thomas M.; Link, Brian K.; Maurer, Matthew J.; Fakhri, Bita; Reddy, Prathima; Smith, Stephen D.; Mukhija, Dhruvika; et al.
Summary: Bendamustine (B) with rituximab (R) is a standard frontline treatment for medically fit follicular lymphoma (FL) patients. The safety and efficacy of maintenance rituximab (MR) after BR induction has not been formally compared to observation for FL, resulting in disparate practice patterns. Prospective trials have shown benefit of MR after R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) or R‐CVP (rituximab, cyclophosphamide, vincristine, prednisone), yet recent data from the GALLIUM study comparing outcomes of patients treated with chemotherapy with R or obinutuzumab (G) showed higher than anticipated fatal adverse events with BR/BG. In order to assess the efficacy and tolerability of MR after BR, we retrospectively collected data on 640 newly diagnosed patients treated with FL. We found that patients who achieved partial remission (PR) after ≥4 cycles of BR had improved duration of response (DOR) with MR vs. no maintenance, whereas those in complete remission did not. These findings were confirmed in a validation cohort. In the entire study population, the known fatal adverse event rate after BR was 2·5% and did not significantly differ in those receiving MR versus no maintenance. [Correction added on 14 January 2019, after online publication: The preceding sentence has been corrected in this current version.] Within the limitations inherent to retrospective analysis, these data suggest that FL patients with a PR to BR experience prolongation of remission with MR with an acceptable safety profile.